Impedance spectroscopy studies of electroless Ni–P matrix, Ni–W–P, Ni–P–ZrO2, and Ni–W–P–ZrO2 coatings exposed to 3.5% NaCl solution. Issue 10 (5th November 2012) - Stankiewicz, A.; Masalski, J.; Szczygieł, B.
Abstract Ni–P matrix, ternary Ni–W–P and Ni–P–ZrO2 coatings, and quaternary Ni–W–P–ZrO2 coatings were deposited using electroless method from a glycine bath. Their corrosion resistance was evaluated by electrochemical impedance spectroscopy (EIS) for various immersion times in a 3.5% NaCl solution. From among the investigated coatings, the ternary Ni–W–P coatings show the highest resistance to corrosion in the first hour of exposure to the 3.5% NaCl medium. An addition of ZrO2 adversely affects the performance of both the Ni–P coatings and the Ni–W–P coatings. For all the coatings, including the ones containing tungsten, a marked decrease in pore resistance (Rpor) over time is observed. This means that their corrosion resistance and capacity to protect the substrate decline. On the other hand, after 24 h immersion in the 3.5% NaCl solution the Ni–W–P coating shows the highest low‐frequency impedance modulus (|Z|f = 0.01 Hz). As regards corrosion resistance, the Ni–P coatings and the Ni–W–P coatings perform best.